(untitled) (Hoboken, NJ., 2006)
Recent work has made great strides toward devising robust adaptive beamformers that vastly improve signal strength against background noise and directional interference. This dynamic technology has diverse applications, including radar, sonar, acoustics, astronomy, seismology, communications, and medical imaging. There are also exciting emerging applications such as smart antennas for wireless communications, handheld ultrasound imaging systems, and directional hearing aids.
Keywords: Adaptive antennas,Antenna radiation patterns,Anten cảm ứng,Antenna bức xạ mẫu